Perbedaan Pengaruh Antara Transcutaneus Electrical Nerve Stimulation (Tens) Dengan Terapi Massage Terhadap Penurunan Nyeri Pada Penderita Nyeri Punggung Bawah Non Spesifik - Septi Ayu Arum Yuspita Sari (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Non-Specific Low Back Pain, Transcutaneous Electrical Nerve Stimulation (TENS), Massage Therapy. The cause of the symptoms of non-specific low back pain is the mechanic's factor because of overload of the spine. Transcutaneous electrical nerve stimulation (TENS) and massage therapy is a method that can be used to decrease pain caused by the occurrence of non-specific low back pain. This study aimed to investigate the effect and influence of the difference between TENS with massage therapy to decrease pain in patients with non-specific low back pain. This study employed an experimental two group pre-test and post-test design. Twelve patients with non-specific low back pain were randomly divided into two groups: TENS (group 1) and massage therapy (group 2). All patients were evaluated before and after treatment using a visual analog scale. Mann Whitney test hypothesis testing in the group of TENS obtained QVAS value p = 0,026, while in the group massage therapy obtained QVAS value p = 0,024 are statistically significant decrease pain. Wilcoxon test result hypothesis between TENS with massage therapy obtained after treatment p = 0,004 means there is a significant difference between TENS with massage therapy. TENS was more effective in improving pain than massage therapy for a patient with non-specific low back pain.